SOCIAL MEDIA FOR ENHANCED BRAND AWARENESS AT POLITEKNIK PENERBANGAN SURABAYA - Julaihah, Siti; Putra, Iwansyah; Thiro Kabul Y, Yudhis; Prasetya Wardhani, Norita (Politeknik Penerbangan Surabaya, 2024)
This research discusses the utilization of YouTube as a social media platform for enhancing brand awareness, particularly for Politeknik Penerbangan Surabaya. The study aims to comprehend how YouTube is used to increase brand awareness, progressing from consumers being unaware of the brand (brand unaware) to achieving brand recognition, brand recall, and ultimately, becoming the top-of-mind choice for consumers when thinking about Politeknik Penerbangan Surabaya. The research methodology employed is qualitative descriptive, involving data collection methods such as observation, interviews, and documentation. Eight informants, including Politeknik Penerbangan Surabaya's management, staff, and students who actively use YouTube, participated in the study. Interactive data analysis models and triangulation techniques were used to ensure data validity. The findings indicate that Politeknik Penerbangan Surabaya effectively utilizes YouTube to bolster brand awareness. Their strategies encompass creating and sharing high-quality video content, showcasing their activities and accomplishments, and employing tactics to increase brand recognition. Furthermore, they consistently upload relevant video content, engage with viewers, and establish emotional connections to enhance brand recall. These efforts have led to Politeknik Penerbangan Surabaya becoming the top-of-mind choice among their target audience.